Sonifying Napoleon's March by Identifying Auditory Correlates of the Graphic-Linguistic Distinction - Coppin, Peter W.; Windeyer, Richard C. (Diagrammatic Representation and Inference, 2018)
Identifying auditory correlates of the graphic-linguistic distinction informs our design of an auditory display based on Charles Minard’s depiction of Napoleon’s Russia campaign – the gold standard for visual (graphic) information design and therefore a grand challenge for auditory display design. We identify viable alternatives to the text-only translations currently employed in making graphics accessible to blind and/or low-vision individuals by introducing sounds bearing strong ecological resemblances to Minard’s depictions. Our integration of theoretical work about classic distinctions with common properties across diagrammatic and auditory display communities reveals practical opportunities for designing inclusive and accessible graphics.